Feeding regimes influence growth, survival, morphometric indicators, and water quality correlations in Betta splendens (Super Red Plakat strain) fry - ZULKISAM PRAMUDIA; AZFAR ISMAIL; MEGA ASRI RISQIANA; YUNITA MAIMUNAH; ANJAS SASANA BAHRI; AGUS FERI SETIAWAN; ANDI KURNIAWAN; TIA DWI IRAWANDANI (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Pramudia Z, Ismail A, Risqiana MA, Maimunah Y, Bahri AS, Setiawan AF, Kurniawan A. 2026. Feeding regimes influence growth, survival, morphometric indicators, and water quality correlations in Betta splendens (Super Red Plakat strain) fry. Biodiversitas 27 (1): d270114. https://doi.org/10.13057/biodiv/d270114. The early larval stage is crucial for growth and survival in ornamental fish culture, yet feeding strategies for Betta splendens (Super Red Plakat strain) remain underexplored. This study evaluated the effects of five feeding regimes, comprising live prey and formulated diets on the morphometric growth and survival of B. splendens fry during a 28-day post-infusoria rearing period. Five dietary treatments: Artemia nauplii, Alona sp., Moina sp., Daphnia magna, and artificial pellets, with infusoria provided in all treatments during the first week. Survival rate (SR), total length (TL), and standard length (SL) were measured at the end of the experiment. Fry fed with Artemia nauplii and Moina sp. exhibited the highest survival (88-89%) and growth performance (TL up to 15.6 mm), while D. magna resulted in the lowest values. Statistical analysis confirmed significant differences among treatments. Water quality remained within optimal thresholds, ensuring reliable interpretation. Pearson correlation analysis showed strong positive associations among SR, TL, and SL, confirming that survival is closely linked to growth. Moderate correlations between DO and biological metrics suggest oxygen availability may indirectly influence performance. These findings highlight the importance of feed type and particle size compatibility with larval open-mouth for enhancing productivity in B. splendens hatchery practices. The use of Artemia or Moina during the post-infusoria stage can enhance hatchery yield by approximately 10-20%, providing practical guidance for sustainable B. splendens aquaculture and supporting SDG 14 (Life Below Water) through improved fry survival and responsible freshwater biodiversity management.